الكلّيات بين الجويني وابن العربي وأثرها في توجيه الخلاف: نظرات في المفهوم والوظيفة: Universals in the Thought of Al-Juwayni and Ibn al-Arabi and their Impact on Directing Disagreement between Rules: The Concept and Function - التركاوي, إدريس (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2014)
تروم الدراسة الكشف عن ترسانة من القواعد التي أخذت طابع الكلّي واصطبغت بصبغته عند الجويني وابن العربي، وتُبرز مكانةَ بعض هذه القواعد -بعد رصد مفهومها وأهم أنواعها- في توجيه الخلاف ببُعْديه: الفقهي والأصولي في سياق الاستدلال على ألوان من القضايا العلمية عند الرجلين؛ ما يُمكِّن من الوقوف على معالم الوحدة المنهجية لأصول المذاهب في بناء القواعد وترجيح الأحكام. This study aims to reveal the set of rules that take the character of the universal (al-Kuliyyat) in the works of both Al-Juwayni and Ibn al-Arabi. After identifying the concepts and varieties of these rules, this study highlights the impact of some of them in directing the disagreement between them in its two dimensions; the fiqh and usul, in the context in which each scholar would establish evidence of certain scholarly issues. This approach helps in understanding the methodological unity of the foundations of intellectual schools of thought (Mathahib) in building rules and weighing different judgments.